ANALISIS KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI PADA MASA PANDEMI COVID-19 - Try Wahyu Utami; Ali Hardana (Jaksya: Jurnal Akuntansi Syariah, 2023)
The purpose of this study was to analyze the performance of banking companies listed on the IDX during the Covid-19 period. The population in this study were all banking companies listed on the Indonesia Stock Exchange for the 2018-2020 period totaling 40 companies, the sample in this study was 34 companies. The data collection method used in this study was purposive sampling. The results showed that the minimum institutional ownership at PT Nusantara Inti Corpora, and the maximum institutional ownership at PT HM Sampoerna, while the standard. Minimum managerial ownership is PT Indomobil Sukses International, maximum managerial ownership is PT Nipress. The minimum company performance is PT Nusantara Inti Corpora, and the maximum company performance is PT Astra Otoparts.